(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2025)
Polypropylene (PP) is widely used in technical textiles, such as protective/safety and home textiles. However, its inherent flammability limits its performance in such contexts. This study investigates the flammability characteristics of PP raw material mixed with organophosphonate-based flame retardant additive. The FR additive was incorporated into the PP matrix at concentrations ranging from 1 % to 8 % using a laboratory-scale melt-spinning process. Pure and FR-treated PP fabrics’ burning and flame spread behaviours were investigated in detail. Flame spread behaviours were further supported by digital photographs and AutoCAD drawings. Results show that the pure PP fabric exhibits double-burning peaks and burns for a long time. Burning lengths and burning time were significantly reduced by adding FR additives. Fabrics with FR treatment predominantly display single-peak and middle-ignition behaviour, indicating improved fire resistance. These findings highlight the effectiveness of organophosphonate-based additives in enhancing the flame retardancy of PP textiles, supporting their safer use in technical applications.